Requisitos profissionais do estudante de engenharia de produção: uma visão através dos estilos de aprendizagem - Freitas, Alessandra Aparecida; Dornellas, Danielle Vasconcellos; Belhot, Renato Vairo (Revista Gestão da Produção Operações e Sistemas, 2006)
Researchers have found strong evidence of different learning styles in students, and they have been investigating the effect of matching and mismatching a style with teaching methods. Many educators aware of how learning styles affect learning have successfully used learning style theories to better understand students and to progressively improve teaching strategies. In order to carry out an exploratory study about the learning styles of the students enrolled at Production Engineering Department of USP - São Carlos, two different learning styles inventories are used: the Index of Learning Styles - ILS and the Temperament Sorter. Both inventories had their use authorized by developers for research purposes. From all the students, 123 answered the Keirsey questionnaire and 121 filled out the Felder e Soloman Index of Learning Styles - ILS. Gathered data indicate predominant dimensions for each learning style inventory. Most of the students that filled out the questionnaires are Active (60%), Sensing (72%), Visual (78%) and Global (55%) according to the ILS. Extrovert (59%), Intuitive (45%), Thinkers (61%) and Judgers (75%) are the majority among them, according to the Temperament Sorter. Keywords: Engineering Education; Learning Styles; Index of Learning Styles; Temperament Sorter.